(untitled) (Research, Society and Development, 2024)
Congenital Syphilis (CS) occurs through transplacental transmission of Treponema pallidum from pregnant women to their children. Therefore, the main objective of this research is to describe the sociodemographic and epidemiological profile of congenital syphilis in the Northeast region of Brazil from 2018 to 2022. The methodological proposal used consists of an epidemiological, retrospective and descriptive study, constructed through the collection of secondary data available on the platforms of the Ministry of Health (MS), the Department of Chronic Conditions and Sexually Transmitted Infections (DCCI) and the Notifiable Diseases Information System (SINAN) of the Unified Health System (SUS) available on the Datasus portal. During the study period, 29,431 cases of congenital syphilis were reported in Northeast Brazil, with the highest concentration of cases in 2021 (n=8,052) and the state with the highest incidence being Pernambuco (n=8,021), followed by the lowest with 1,359 cases, Piauí. It was also found that the CS detection rates in this research exceeded the global incidence rate, which corresponds to 4.98 cases/1000 live births. From the data it was found that there is still a gradual increase in CS cases, which raises reflections on the quality of care for pregnant women. To this end, health education measures are necessary, as well as improvements in the care provided to this population group.